TRANSFORMATIVE EFFECTS OF DIGITALIZATION ON POSTAL SAVING SCHEMES IN A POST-DEMONETIZATION ERA - Chhibber, Prannay; Ahmed, Mohd Arsalan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the transformative effects of digitalization on postal saving schemes in the aftermath of demonetization. Analyzing Likert-scale responses from 230 users, the research identifies nuanced user perceptions across five key aspects: user-friendliness, security measures, confidence in digital platforms, belief in additional digital features, and trust in technological adaptability. The findings highlight opportunities for improvement, emphasizing the importance of user-centric enhancements, robust security measures, and transparent communication to foster trust in a digitally-driven financial landscape. The study contributes a roadmap for optimizing digital strategies within postal saving schemes, navigating the balance between historical roots and technological advancements in a post-demonetization era.